Unveiling the Role of Cross-Cultural and Cognitive Differences in Organizational Learning Mechanism of Technology-Acquiring Cross-Border Mergers and Acquisitions: Evidence From Emerging Market Enterprises - Chen, Kanxiang; Cheng, Xuanmei; Zhang, Run; Cillo, Giuseppe; Ragusa, Antonio (Frontiers in Psychology, 2022)
In recent years, cross-border mergers and acquisitions of emerging market enterprises have increased rapidly, and a large number of technology sourcing cross-border mergers and acquisitions have been carried out to the United States, Western Europe and other developed countries. This new type of technology-acquiring cross-border M&A presents many unique features. In particular, the cross cultural differences between home country and host country and the cognitive differences between emerging markets and developed markets pose a huge challenge to the organizational learning of technology-acquiring cross-border M&A of enterprises from emerging markets. Based on this, this paper innovatively constructs an integrated theoretical model to explore the role of cross cultural and cognitive differences in organizational learning mechanism of technology-acquiring cross-border M&A in emerging markets. In this paper, partial least squares structural equation model (PLS-SEM) is used through the empirical study of 240 Chinese technology-acquiring cross-border M&A enterprises, it is found that cultural differences and cognitive differences play an important role in technical ability and learning performance. The study also found that the interaction of cross cultural differences between home country and host country and cognitive differences between emerging markets and developed markets promoted the learning performance of cross-border M&A in emerging markets.